Social Policy in Changing European Societies (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Adopting an interdisciplinary approach this book provides a cutting-edge, in-depth account of social policy research today, how we got here, and where future research should be headed. It defines the core research agenda for the future covering multiple social policy fields, including care, family, health, and housing policy as well as gender equality, labour market policy, and welfare attitudes.